What the hippocampus tells the HPA axis: Hippocampal output attenuates acute stress responses via disynaptic inhibition of CRF+ PVN neurons - Anthony B. Cole; Kristen Montgomery; Tracy L. Bale; Scott M. Thompson (Neurobiology of Stress, 2022)
The hippocampus exerts inhibitory feedback on the release of glucocorticoids. Because the major hippocampal efferent projections are excitatory, it has been hypothesized that this inhibition is mediated by populations of inhibitory neurons in the hypothalamus or elsewhere. These regions would be excited by hippocampal efferents and project to corticotropin-releasing factor (CRF) cells in the paraventricular nucleus of the hypothalamus (PVN). A direct demonstration of the synaptic responses elicited by hippocampal outputs in PVN cells or upstream GABAergic interneurons has not been provided previously. Here, we used viral vectors to express channelrhodopsin (ChR) and enhanced yellow fluorescent protein (EYFP) in pyramidal cells in the ventral hippocampus (vHip) in mice expressing tdTomato in GABA- or CRF-expressing neurons. We observed dense innervation of the bed nucleus of the stria terminalis (BNST) by labeled vHip axons and sparse labeling within the PVN. Using whole-cell voltage-clamp recording in parasagittal brain slices containing the BNST and PVN, photostimulation of vHip terminals elicited rapid excitatory postsynaptic currents (EPSCs) and longer-latency inhibitory postsynaptic currents (IPSCs) in both CRF+ and GAD + cells. The ratio of synaptic excitation and inhibition was maintained in CRF + cells during 20 Hz stimulus trains. Photostimulation of hippocampal afferents to the BNST and PVN in vivo inhibited the rise in blood glucocorticoid levels produced by acute restraint stress. We thus provide functional evidence suggesting that hippocampal output to the BNST contributes to a net inhibition of the hypothalamic-pituitary axis, providing further mechanistic insights into this process using methods with enhanced spatial and temporal resolution.